2010
DOI: 10.1097/inf.0b013e3181d285ac
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Fosamprenavir in Human Immunodeficiency Virus-Infected Pediatric Patients

Abstract: Fosamprenavir (FPV) efficacy in human immunodeficiency virus (HIV)-infected pediatric patients is still being evaluated in ongoing clinical trials. The long-term efficacy and safety of FPV boosted with ritonavir (FPV/r) was evaluated in 20 antiretroviral-naive and antiretroviral-experienced HIV-vertically infected pediatric patients. Analyses of CD4(+) T-cells, HIV-ribonucleic acid (RNA), and clinical status were performed during a median of 180 weeks. Initially, median HIV-RNA was 4.6 log(10) in naive and 4.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Palladino et al . studied 20 HIV‐infected children over a median of 180 weeks and reported sustained antiviral response and immunological improvement …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladino et al . studied 20 HIV‐infected children over a median of 180 weeks and reported sustained antiviral response and immunological improvement …”
Section: Introductionmentioning
confidence: 99%
“…Palladino et al studied 20 HIV-infected children over a median of 180 weeks and reported sustained antiviral response and immunological improvement. 5 We conducted a pharmacoepidemiology study to assess the use and long-term safety of FPV in children in 'real world' clinical settings in Europe. Individual patient data originated from cohorts participating in the European Pregnancy and Paediatric HIV Cohort Collaboration (EPPICC), a network of European cohorts of prospectively observed mother-child pairs and children within EuroCoord (www.eurocoord.net).…”
Section: Introductionmentioning
confidence: 99%
“…We have a follow-up of the HIV-infected children in the CoRISpe database of the Paediatric Units and we have been working with these data obtaining interesting results as it is seen in a great number of our published articles [8,16,33-44]. Moreover, the CoRISpe has been collaborating with different European Cohorts (EPPICC, COHERE and PENTA) for many years.…”
Section: Discussionmentioning
confidence: 98%
“…We have done seven research projects with the data provided by the CoRISpe and/or with the samples supplied by the BioBank. The results of all these projects are available to the paediatricians participating in the CoRISpe with a view to improving the state of health of their patients [8,33-44]. …”
Section: Introductionmentioning
confidence: 99%
“…Es una sulfamida por lo que se debe usar con precaución en pacientes con alergia a sulfas. Se administra dos veces por día en pacientes pediátricos 46 . Las dosis se muestran en la Tabla 5.…”
Section: Darunavir (Drv)unclassified